DIURNAL VARIATIONS IN BLOOD PRESSURE AND THEIR RELATION WITH CAROTID ARTERY INTIMA-MEDIA THICKENING - Shahin Narooei; Behzad Soroor Azimzadeh; Farid Zaker (ARYA Atherosclerosis, 2010)
Abstract  INTRODUCTION: Hypertension is a very common cardiovascular disease with extensive effects on body organs. This study was conducted to compare the extent of target organ damage in hypertensive patients with and without significant nocturnal fall in blood pressure (dippers and non-dippers, respectively). methods: One-hundred patients with recently diagnosed hypertension underwent 24-hour ambulatory blood pressure monitoring and carotid Doppler ultrasonography. They were divided into patients with nocturnal fall in blood pressure (dippers) and without nocturnal fall in blood pressure (non-dippers). results: Sixty-five patients with nocturnal systolic blood pressure fall greater than 10% (dippers) were matched for age, sex, body mass index (BMI) and body mass area (BMA) with 35 patients with less than 10% fall in nocturnal blood pressure (non-dippers). The two groups were not different in terms of ambulatory and mean 24-hour blood pressure. Assessments showed significantly greater carotid intima-media thickening in the non-dipper group. Discussion: This study suggests that a reduced nocturnal fall in blood pressure may play a pivotal role in the development of some features of target organ damage such as carotid intima-media thickening, despite similar clinical findings and no significant difference in mean 24-hour blood pressure. Keywords • Hypertension • Ambulatory blood pressure monitoring • Carotid intima-media thickness • Carotid color Doppler sonography